ASSISTANCE IN SUSTAINABLE LIVESTOCK BUSINESS MANAGEMENT BASED ON THE EMPOWERMENT OF SMALLHOLDER FARMERS AS AN EFFORT TO STRENGTHEN NATIONAL FOOD SECURITY - Ibrahim; Asmaul Husna (CV. Naskah Aceh, 2026)
National food security is a strategic issue that requires support from various sectors, including the livestock sector. However, most smallholder livestock enterprises still face challenges in business management, production efficiency, and sustainable management practices. This community service program aims to provide assistance in sustainable livestock business management as an effort to strengthen national food security. The implementation methods include identifying partners’ problems, conducting training on livestock business management, providing assistance in production management and business record-keeping, and evaluating program sustainability. The target beneficiaries are livestock farmer groups who are expected to improve their knowledge, skills, and independence in managing livestock businesses effectively and sustainably. The results of the program indicate an improvement in partners’ understanding of livestock business management, production planning, and awareness of the importance of business sustainability. This program is expected to make a tangible contribution to strengthening national food security through enhancing the capacity of community-based livestock enterprises.